COVID‐19 pandemic impact on cytopathology practice in the post‐lockdown period: An international, multicenter study. Issue 5 (10th January 2022) - Vigliar, Elena; Pisapia, Pasquale; Dello Iacovo, Filippo; Alcaraz‐Mateos, Eduardo; Alì, Greta; Ali, Syed Z.; Baloch, Zubair W.; Bellevicine, Claudio; Bongiovanni, Massimo; Botsun, Pavlina; Bruzzese, Dario; Bubendorf, Lukas; et al.
Abstract : Background: In a previous worldwide survey, the authors showed a drastic reduction in the number of cytological specimens processed during the coronavirus disease 2019 "lockdown" period along with an increase in malignancy rates. To assess the continued impact of the pandemic on cytological practices around the world, they undertook a second follow‐up worldwide survey collecting data from the post‐lockdown period (2020). Methods: Participants were asked to provide data regarding their cytopathology activity during the first 12 weeks of their respective national post‐lockdown period (2020), which ranged from April 4 to October 31. Differences between the post‐lockdown period and the corresponding 2019 period were evaluated, and the authors specifically focused on rates of malignant diagnoses. Results: A total of 29 respondents from 17 countries worldwide joined the survey. Overall, a lower number of cytological specimens (n = 236, 352) were processed in comparison with the same period in 2019 (n = 321, 466) for a relative reduction of 26.5%. The overall malignancy rate showed a statistically significant increase (12, 442 [5.26%] vs 12, 882 [4.01%]; P < .001) during the same time period. Similar results were obtained if both malignancy and suspicious for malignancy rates were considered together (15, 759 [6.58%] vs 16, 011 [4.98%]; P < .001). Conclusions: The data showed a persistent reduction in the cytological specimen volume during the post‐lockdown period (2020). However, the relative increase in the cytological workload in the late part of the post‐lockdown is a promising finding of a slow return to normality. Abstract : A persistent reduction in the cytological specimen volume during the post‐lockdown period has been observed. The relative increase in the cytological workload in the late part of the post‐lockdown period is a promising finding of a slow return to normality.